Heat dissipation analysis of different flow path for parallel liquid cooling battery thermal management system. (26th March 2020) - Yang, Yi; Li, Wenchao; Xu, Xiaoming; Tong, Guangyao
Summary: As the main form of energy storage for new energy automobile, the performance of lithium‐ion battery directly restricts the power, economy, and safety of new energy automobile. The heat‐related problem of the battery is a key factor in determining its performance, safety, longevity, and cost. In this paper, parallel liquid cooling battery thermal management system with different flow path is designed through changing the position of the coolant inlet and outlet, and the influence of flow path on heat dissipation performance of battery thermal management system is studied. The results and analysis show that when the inlet and the outlet are located in the middle of the first collecting main and the second collecting main, respectively; system can achieve best heat dissipation performance, the highest temperature decrease by 0.49°C, while the maximum temperature difference of system decreases by 0.52°C compared with typical Z‐type BTMS under the discharge rate of 1 C. Then an optimization strategy is put forward to improve cooling efficiency compared with single‐inlet and single‐outlet symmetrical liquid cooling BTMS; the highest temperature of three‐inlet and three‐outlet is 27.98°C while the maximum temperature difference of three‐inlet and three‐outlet is 2.69°C, decrease by 0.7 and 0.67°C, respectively. Abstract : In this paper, parallel liquid cooling battery thermal management system with different flow path is designed through changing the position of the coolant inlet and outlet, and the influence of flow path on heat dissipation performance of battery thermal management system is studied.